Application of Coppeng (Syzygium Cumini L) Fruit Extract in Developing Instant Noodles with Antioxidant Properties - Rezkyani, Aprilyanti Nur; Yanto, Subari; Putra, Reski Praja (Agricultural Technology Education Study Program, 2024)
Coppeng fruit (Syzygium cumini L) is one of the local fruits in Indonesia, especially in Makassar, South Sulawesi. This fruit has many benefits and can act as an anthocyanin antioxidant, and the bioactive content of coppeng fruit extract is also known to act as an anti-inflammatory, worm medicine, anticancer, antibacterial, and antidiabetic. The purpose of this study was to determine the effect of coppeng fruit extract concentration on the physicochemical quality and microbiological contamination of the instant noodles produced and to determine the effect of coppeng fruit extract concentration on the hedonic quality and functional properties of the instant noodles produced. This research method is a quantitative experiment, namely the development of functional instant noodles by utilizing coppeng fruit extract. This study used a Completely Randomized Design (CRD) with 3 replications with the addition of coppeng fruit extract concentrations of 0%, 12%, 14%, and 16%. The results showed that the addition of coppeng fruit extract concentration had a significant effect on the instant noodles produced. The color change of the noodle dough occurred after the addition of a concentration of 12% and the instant noodles produced had met the SNI instant quality standards (01-3551-2000). The best instant noodles were produced from the treatment of coppeng fruit extract concentration of 14%, these noodles have characteristics, namely water content of 3.83%, ALT 4.7 Log colonies/ml, polyphenol content of 8.43%, anthocyanin content of 1.1900 ppm, antioxidant content of 10.57%.